Algeria Economic Update - Fall 2021 : Restoring the Algerian Economy after the Pandemic (Washington, DC: World Bank, 2022)
Algeria is enjoying temporarily breathing space, as hydrocarbon prices reach new highs and the Coronavirus (COVID-19) pandemic eases. After peaking during the summer, the number of daily Coronavirus (COVID-19) cases plummeted in the Fall, while the vaccination campaign accelerated. Meanwhile, global oil and gas prices are reaching levels unseen since before the 2014 oil crisis, allowing for a gradual recovery in crude oil production quotas, and a surge in natural gas production and exports. Surging hydrocarbon exports revenues are contributing to a marked decline in external financing needs and to the short-term stabilization in growing domestic financing needs. Meanwhile, the economic recovery in non-hydrocarbon sectors lost steam, remaining largely incomplete, while inflationary risks are materializing. Absent decisive implementation of the reform agenda, the economic outlook points to a fragile recovery, and to deteriorating fiscal and external balances in the medium-term. Algeria’s intact dependance on hydrocarbon revenues, the spread of new Coronavirus (COVID-19) variants and the pace of the announced reform effort remain the key sources of risks to the outlook.